Midiatização do jornalismo esportivo em ambiente digital: interações entre produtores e receptores em blogs dos websites Espn-Estadão, Sportv, Placar e Lancenet - Souza Júnior, Arnaldo Oliveira (Universidade do Vale do Rio dos Sinos, 2014)
The sports journalistic blog appears as a new area of contact and participation of Internet users, by offering their web communication protocols, causing changes in the relationship between producers and receivers in the process of social interaction. The objective of this research is to analyze how the processes and interactions that occur by virtue of the practices of mediatization of producers and receivers are carried on the interaction in sports blogs. The research is presented as a multiple case study on 04 ( four) blogs belonging to portals and websites sporting arena, whose brands are television and print media, in which investigates the processes and operations of mediatization manifested in them, aiming the production of interaction with readers . The object of study generates as a question: how the processes and operations of mediatization take place in interactions in sports blogs? It is researched Paulo Vinicius Coelho blog - PVC, Espn - Estadão, in Blog Games that I saw, the journalist Lédio Carmona, the Slav, the Blog Serginho , journalist Sérgio Xavier, the site of Score Magazine , and Chat with Benja on blog of journalist Benjamin Back, site Lancenet. The study is being performed to concepts that reflect the issue of media coverage of social practices, theory based mainly in Braga (2007), Castells (2013), Fausto Neto (2006), Hjarvard (2012) and Veron (2007), offering subsidies for analysis of the object here proposed. The analysis of selected blogs is by means of categories, organized into three areas: the architecture of devices, producers and receivers interactions and discursive movement. The category analysis shows the following results: the quality of the architecture and structure of the media affects their ability to interact; discourses seek to establish bonds of interaction between producers and receivers, manifesting a high loyalty of readers to bloggers journalists, and there are particularities movements of discursive circulation, according mediatization processes and operations that occur in each blog studied. The findings show that the processes and operations of mediatization produce very complex communicational effects and engender new modes of interactions in the relationship between producers and receivers in digital ambience of sports blogs, culminating in discursive movement and the formation of new circuits of information.
Keywords: Midiatização; Jornalismo esportivo; Blog; Dispositivo de interação; Circulação discursiva; Mediatization; Sports journalistic; Interaction device; Discursive circulation; ACCNPQ::Ciências Sociais Aplicadas::Comunicação